Revision der Gattung Nanna Birket-Smith, 1965 (Lepidoptera, Arctiidae, Lithosiinae). - Kühne, Lars (Contributions to Entomology = Beiträge zur Entomologie, 2014)
The Afrotropical genus Nanna Birket-Smith, 1965 is revised. Seven new species and two new subspecies are described: broetheri sp. nov., hoppei sp. nov., distyi sp. nov., eningae albifrons ssp. nov., eningae subflava ssp. nov., tanzaniae sp. nov., luteolata sp. nov. griseoides sp. nov. and falcata sp. nov. The status of pia (Strand, 1912) is revised (stat. rev.) and a lectotype is signed. The taxon magna Birket-Smith, 1965 is a synonym (syn. nov.) of pia Strand. Keywords Lepidoptera, Arctiidae, Lithosiinae, genus Nanna, revision, taxonomy, Africa. Nomenclatural Acts broetheri Kühne, 2014 (Nanna), spec. n. distyi Kühne, 2014 (Nanna), spec. n. falcata Kühne, 2014 (Nanna), spec. n. griseoides Kühne, 2014 (Nanna), spec. n. hoppei Kühne, 2014 (Nanna), spec. n. luteolata Kühne, 2014 (Nanna), spec. n. magna Birkett-Smith, 1965 (Nanna), syn. n. of Nanna pia (Strand, 1912) pia (Strand, 1912) (Nanna), stat. n. described as Eilema eningae, var. pia Strand, 1912 tanzaniae Kühne, 2014 (Nanna), spec. n. albifrons Kühne, 2014 (Nanna eningae), subspec. n. subflava Kühne, 2014 (Nanna eningae), subspec. n.